2009
DOI: 10.1158/1078-0432.ccr-09-1001
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk to Stromal Fibroblasts Induces Resistance of Lung Cancer to Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors

Abstract: Purpose: Lung cancers with epidermal growth factor receptor (EGFR)-activating mutations show good clinical response to gefitinib and erlotinib, selective tyrosine kinase inhibitors (TKI) to EGFR, but these tumors invariably develop drug resistance. Host stromal cells have been found to have a considerable effect on the behavior of cancer cells. Little is known, however, about the role of host cells on the sensitivity of cancer cells to receptor TKIs. We have therefore assessed the effect of crosstalk between s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
217
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 258 publications
(229 citation statements)
references
References 33 publications
10
217
1
1
Order By: Relevance
“…The notion that the pronounced desmoplastic reaction in PDA actively contributes to the unusual refractoriness of PDA to systemic therapies has stimulated this area of research and revealed candidate therapeutic targets. Nonetheless, a potential role for desmoplasia in drug resistance has been only partially addressed, due to the multitude of signaling interactions between tumor cells and the surrounding microenvironment (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…The notion that the pronounced desmoplastic reaction in PDA actively contributes to the unusual refractoriness of PDA to systemic therapies has stimulated this area of research and revealed candidate therapeutic targets. Nonetheless, a potential role for desmoplasia in drug resistance has been only partially addressed, due to the multitude of signaling interactions between tumor cells and the surrounding microenvironment (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Using in vitro and animal models, Wang et al previously demonstrated that crosstalk to stromal fibroblasts via hepatocyte growth factor (HGF) induces resistance of NSCLC to EGFR-TKIs. 24 Interestingly, serum HGF has been strongly related to the outcome of EGFR-TKI treatment. 25 TAMs may participate in EGFR-TKI resistance by supporting the formation and function of fibroblasts in the stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Despite impressive initial clinical responses, patients with EGFR-mutated adenocarcinomas almost inevitably develop drug resistance after B1 year of TKI treatment. 185,186 Studies have revealed several molecular mechanisms that may contribute to the development of tumor resistance to TKI therapy, 71,84,186,187 including acquired secondary EGFR mutation, activation of alternative signaling pathways that bypass the EGFR pathway, overexpression of HGF, 122 tyrosine protein kinase MET amplification, 53,124 epigenetic factors, 188 constitutive activation of signaling pathways downstream of EGFR, 13,189 tumor stromal and extracellular matrix alterations, 190,191 or host-related mechanisms such as rapid drug inactivation and ATP-binding cassette transporters efflux. 192 …”
Section: Mechanisms Of Resistance To Egfr Targeted Therapymentioning
confidence: 99%